Correlation between Organizational Culture and Organizational Commitment of Nurses at Hamadan University of Medical Sciences, Iran - Zahra Marziyeh Hassanian; Fatemeh Karbasi; Arezoo Shayan; Leilli Tapak (مراقبت پرستاری و مامایی ابن سینا, 2023)
Background and Objective: Organizational commitment of employees is one of the important variables in the effectiveness of organizations. One of the effective factors of nurses' organizational commitment is the organizational culture of health centers. The present study aimed to investigate the correlation between the organizational culture and organizational commitment of nurses at Hamadan University of Medical Sciences. Materials and Methods: This descriptive correlational study was conducted based on an analytical design. The statistical population included all nursing staff working in the educational and medical centers of Hamadan. The sample size was calculated at 257 nurses. Data were collected using the Denison Organizational Culture Standard Questionnaire and the Meyer and Allen Standard Organizational Commitment Questionnaire. In this study, SPSS software (version 16) was used for data analysis, and a p-value less than 0.05 was considered statistically significant. Results: Based on the results, the organizational culture showed a significant correlation with organizational commitment (P <0.001,r = 0.56) and its dimensions, including emotional commitment (P<0.001, r =0.5), continuous commitment (P <0.001, r =0.4), and normative commitment (P <0.001, r =0.38). Moreover, the organizational commitment had a significant relationship with the dimensions of organizational culture, including involvement in work (P <0.001, r =0.48), adaptability (P <0.001, r =0.52), compatibility (P <0.001, r =0.5), and mission (P = 0.001, r =0.5). Conclusion: As evidenced by the obtained results, there was a correlation between organizational culture and dimensions of organizational commitment of nurses. Therefore, it is suggested that managers make wise decisions to promote organizational culture and organizational commitment in medical centers.